1996
DOI: 10.1111/j.2044-8260.1996.tb01208.x
|View full text |Cite
|
Sign up to set email alerts
|

Ways of coping with psychological distress after trauma

Abstract: One hundred and eight survivors of trauma attending a stress clinic were assessed on measures of coping, personality, control expectancies and psychological distress. The psychometric characteristics of these questionnaires are discussed, and the relationships between them investigated using correlational and regression techniques. Although cross-sectional studies can only be indicative, it would appear that most coping strategies, and particularly escape-avoidance, are consistently associated with high psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
9

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 19 publications
4
38
0
9
Order By: Relevance
“…However, due to the cross-sectional nature of this study, it cannot be deemed that such strategies were causal factors in the development of PTD, as they may simply be epiphenomena. 28 Although there were significant differences between the two samples on a number of coping strategies, previous research has not found these strategies under question to be predictive of depression, bar active coping.…”
Section: Discussionmentioning
confidence: 88%
“…However, due to the cross-sectional nature of this study, it cannot be deemed that such strategies were causal factors in the development of PTD, as they may simply be epiphenomena. 28 Although there were significant differences between the two samples on a number of coping strategies, previous research has not found these strategies under question to be predictive of depression, bar active coping.…”
Section: Discussionmentioning
confidence: 88%
“…Ainsi, l'évaluation cognitive représenterait un facteur médiateur de la relation entre un événement stressant comme la perte de ressources et les stratégies d'adaptation (Furukawa, Sarason & Sarason, 1998;Kanninen, Punamaki & Qoûta, 2002;Major et al, 1998). (Arata et al, 2000;Brown et al, 2002;Charlton & Thompson, 1996;North, Smith, McCool & Lightcap, 1989;Smith, 1996 (Holahan & Moos, 1985). L'utilisation plus fréquente des stratégies de distanciation et d'évitement, quelques mois à la suite d'un désastre, est habituelle chez les sinistrés (Suis & Fletcher, 1985).…”
Section: Evaluation Cognitiveunclassified
“…L'utilisation plus fréquente des stratégies de distanciation et d'évitement, quelques mois à la suite d'un désastre, est habituelle chez les sinistrés (Suis & Fletcher, 1985). Horowitz (1980) (Bjorck, Cuthbertson, Thurman & Lee, 2001;Charlton & Thompson, 1996;Morgan, Matthews & Winton, 1995;Murphy, 1986;North et al, 1989;Smith, 1996). (Morgan et al, 1995).…”
Section: Evaluation Cognitiveunclassified
See 1 more Smart Citation
“…For instance, the fact that elements of PD can be categorised as containing aspects of exposure therapy, it is possible that the timing and method of intervention may go some way to ''increasing'' fear through a negative re-appraisal of the events to which they have been subjected (Davey, 1993). While it is generally understood that revisiting and habituating to a traumatic experience is an aid to emotional and cognitive processing, people may, in fact, need a period of distancing allowing minimisation of the event to decrease the perceived danger (Charlton and Thompson, 1996;Gist & Woodall, 1999). In effect, processes of short-term denial, amnesia and numbing about the traumatic experience may be a normal adaptive response to an extreme situation that allows for a period of respite (Creamer, Burgess, & Pattison, 1992;Litz et al, 2002).…”
Section: Introductionmentioning
confidence: 99%